A Comprehension Transfer of Wahabiyah in Recitation System in Dayah Tradisional Aceh - Ernita Dewi; Eka Januar (Universitas Islam Negeri (UIN) Salatiga, 2019)
Wahabiyah which is claimed as a heretical ideology since it is not in line with Ahlul Sunnah Wal Jamaah stated by Tengku (ustad) in Pesantren become the research area in this study. This ideology is presumably from some acts of worship suh as not reading Qunut during Shubuh prayer and doing eigtht-rak’ah tarawih prayer. Furthermore, Wahabi is also pinned on to someone who does not participate in celebrating Prophet Muhammad birthday (Maulid Nabi). This tradition is celebrated in 4 months consecutively in the form of kenduri (thanksgiving by bringing rice and some dishes to the mosque). Someone is appointed when she/he meets the requirements in which explained by the teacher in Pengajian. The problem lies when santri spontaneously labels everyone who does not follow rules of Ahlul Sunnah Wal Jamaah as Wahabi, including Muhammadiyah.